Theoretical and experimental analysis of photovoltaic module characteristics under different partial shading conditions - Ali Hussein Numan; Zahraa Salman Dawood; Hashim A. Hussein (Institute of Advanced Engineering and Science, 2020)
Recently, the renewable energy resources have gained more attention in the electricity sector as promising technology to tackle the depletion in the traditional energy resources. Solar energy grows rapidly due to its vast applications. The performance of Photovoltaic (PV) system is affected by partial shading that results from building, clouds, and fallen leaves. This paper investigates theoretically and experimentally the impacts of various cases of partial shading; such as vertical string, horizontal string, and single cell at environmental conditions on the current-voltage and power-voltage characteristics of 88 W PV panel. In addition, diagonal shading with multi steps is considered in the analysis. The experiments are conducted with considering various parameters; such as shading position and ratio to validate the simulated results. The results show that at 100% shading condition, the maximum power drops by 99.36 %, 43.7%, and 41.15% for horizontal, cellular and vertical shading at the same solar radiation level comparing with their initial state value. Horizontal string shaded has the highest negative impact on the power and efficiency among other types of shadings. The comparison between the theoretical and experimental results reveals considerable agreement between the theoretical and experimental results.